The Effect of Enviromental Score, Social Score and Governance Score Toward Financial Performance - Africa, Laely Aghe; Dwiati, Agustina Ratna; Nahumury, Joicenda (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This research aims to analyze the influence of Enviromental Score, Social Score and Governance Score on the Financial Performance in non Financial companies listed on the Indonesia Stock Exchange for the period 2019-2021 Design/methodology/approach: The sampling method used is purposive sampling method. Data analysis using SPSS 24.0 test tool by descriptive statistics, classic assumption test, multiple linear regression test and hypothesis test Findings: The results showed that Enviromental Score, Social Score and Governance Score not significant to financial performance which measured with stock performance there are PER (Price Earning Ratio) and DPR (Devidend Payout Ratio). These considerations are expected to have a good information about Enviromental Score, Social Score and Governance Score to investor that has no effect to stock performance for. Research limitations/implications: The limitation of this study is that there are many companies that have not fully implemented the ESG (Environmental, Social and Governance) report as a whole so that there is a lot of reduced data that has previously been selected as a research sample. Practical implications: Can be used by company management policies in determining what strategy to use in increasing ESG (Environmental, Social and Governance) scores and financial performance. And indirectly, an increase in ESG (Environmental, Social and Governance) and financial performance scores can increase the attractiveness of potential investors and investors so that companies can grow more rapidly and survive with a better level of health. Originality/value: Originality Paper type: Research paper